2010
DOI: 10.1007/s11095-010-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component Polymeric System for Tumour Cell-Specific Gene Delivery Using a Universal Bungarotoxin Linker

Abstract: We have shown that the presented Ad-PHPMA-BTXbp/scFv-BTX system can be used as a universal tool for a receptor-specific virotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Using a universal bungarotoxin (BTX) linker, non-covalent and non-destructive attachment of a recombinant Ab fragment to pHPMA-modified Ad vectors has been introduced (151). The principle of this strategy is based on the strong and non-covalent interaction between acetylcholine receptors and a-BTX.…”
Section: Active Targetingmentioning
confidence: 99%
“…Using a universal bungarotoxin (BTX) linker, non-covalent and non-destructive attachment of a recombinant Ab fragment to pHPMA-modified Ad vectors has been introduced (151). The principle of this strategy is based on the strong and non-covalent interaction between acetylcholine receptors and a-BTX.…”
Section: Active Targetingmentioning
confidence: 99%
“…The application of protein A or G has allowed antibodies or ligands bearing the Fc domain of immunoglobulin to be linked to therapeutics with high affinity whilst preserving receptor binding regions (17,18). Similar strategies have also been reported utilising the even higher affinity interaction between bungarotoxin and its ligand (19). …”
Section: Introductionmentioning
confidence: 58%
“…The reported difficulties of synthesising and using sialyl Lewis(X) (36) and our previous experience comparing anti-selectin antibodies to the PSGL1 ligand for retargeting of adenovirus vectors (17) persuaded us that the PSGL1 ligand would provide optimal ease of use, efficiency of targeting and reduced immunogenicity. Previous studies have also demonstrated the advantage of attaching targeting ligand to therapeutic agent in ways that use epitopes of the ligand that are not involved in receptor binding and achieve appropriate orientation of the ligand (37) (19). To meet this requirement we developed a new protein G-streptavidin biomaterial as a linker between biotin on the liposome surface and Fc regions in the PSGL1.…”
Section: Discussionmentioning
confidence: 99%
“…Although several sophisticated methods to achieve the site‐specific covalent modification of proteins have been recently described, the formation of a specific noncovalent bond between two peptide tags is an equally attractive approach. Among the various noncovalent methods, the utilization of coiled coil heterodimers, the hybridization of complementary morpholino oligonucleotides and the formation of a complex between bungarotoxin and a bungarotoxin‐binding peptide for the attachment of biologically active proteins to polymer carriers are particularly notable.…”
Section: Introductionmentioning
confidence: 99%